A Model for Using ChatGPT in Attracting and Selecting Human Resources (UNWE Yearbook, 2024)
Technologies are critical to professional success, regardless of our attitude toward them. Digital agility is becoming a leading competency of HR professionals. Expertise in conducting interviews in Microsoft Teams and/or organizing online team meetings is no longer enough. One of the study's main results is that the use of ChatGPT increases the efficiency of the attraction and selection process. The conducted experiment proves that ChatGPT is useful only when the one who uses it has fundamental knowledge of the issues sought in ChatGPT.